Review of animal studies on antimicrobial catheters to prevent catheter-related infections - Bach, Alfons (Zentralblatt für Bakteriologie, 1995)
Various experimental models have been developed to investigate the pathogenesis of intravascular catheter-related infections. Catheters are implanted either subcutaneously or intravenously, and the test animals are inoculated via either the subcutaneous tissue near the catheter exit site or the bloodstream. Catheters containing antimicrobial agents were investigated in various test models and their efficacy in inhibiting bacterial colonisation and reducing catheter-related infections was demonstrated.
Elektronische Reproduktion der Druck-Ausgabe 8. November 2011
Gesehen am 28.11.2023